2010
DOI: 10.2147/ijwh.s8632
|View full text |Cite
|
Sign up to set email alerts
|

Partner violence during pregnancy: prevalence, effects, screening, and management

Abstract: The purpose of this review is to provide an overview of the current state of knowledge regarding the experience of intimate partner violence (IPV) during pregnancy. Pregnancy IPV is a significant problem worldwide, with rates varying significantly by country and maternal risk factors. Pregnancy IPV is associated with adverse newborn outcomes, including low birth weight and preterm birth. Many mechanisms for how IPV may impact birth outcomes have been proposed and include direct health, mental health, and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
202
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(232 citation statements)
references
References 163 publications
(213 reference statements)
7
202
1
10
Order By: Relevance
“…Embora as variáveis nível de ansiedade moderada/alta e violência não tenham apresentado associação significante, registraram altos valores de OR. Provavelmente a baixa prevalência do evento influenciou a não associação, uma vez que outros estudos 29,30,31 associam violência ao uso de drogas ilícitas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora as variáveis nível de ansiedade moderada/alta e violência não tenham apresentado associação significante, registraram altos valores de OR. Provavelmente a baixa prevalência do evento influenciou a não associação, uma vez que outros estudos 29,30,31 associam violência ao uso de drogas ilícitas.…”
Section: Discussionunclassified
“…A maior parte dos pesquisadores em saúde mental concorda que há poucas diferenças entre as chamadas drogas lícitas e ilícitas, pois o impacto subjetivo sobre o indivíduo se torna irrelevante após certo tempo de consumo 31,35 .…”
Section: Discussionunclassified
“…More consideration of support and interventional strategies (Bailey, 2010;Campbell, 1998;McFarlane et al, 2000;Winn et al, 2003) which may ameliorate the relationship between prenatal stress and fetal well-being is also needed.…”
Section: Multidimensional Scale Of Perceived Social Support and The Cmentioning
confidence: 99%
“…[2][3][4][5] Violence against women has been found to constitute violation of the human rights of the affected women. 6,7 While violence against women generally carries lots of adverse health consequences on the victims, violence against pregnant women is associated with double burden of complications on the pregnant women and the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that domestic violence could result in both short and long term several complications and severe morbidities that could jeopardize the health and life of both pregnant women and the fetus, leading to family dysfunction and cascade of several other problems to the society. 2,[8][9][10][11] In a study on violence against women during pregnancy, Messa, etal had shown that repercussion of violence against women during pregnancy way include abortion, preterm labour, chronic pelvic pain, headaches, depression, attempted suicide, post traumatic stress disorder (PSTD), anxiety, drug abuse for the mother; intrauterine fetal retardation, low birth weight, fetal loss, increased rate of prenatal morbidity for the fetus. As appalling and deleterious as domestic violence against pregnant women is, it has been shown that its prevalence continues to be high globally especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%